Implementasi Kebijakan Perlindungan Hutan Di Kesatuan Pengelolaan Hutan Balantak Kabupaten Banggai Provinsi Sulawesi Tengah - Fitriani Abdullah; Yunus Papea (Jurnal ADMINISTRATOR, 2021)
This study focuses on the purpose of knowing and describing the implementation of forest protection policies in the Balantak Forest Management Unit, Banggai Regency, Central Sulawesi Province. The usefulness of this research is Theoretical and Practical. The Literature Review explains the concept of public administration, the concept of public policy, the concept of policy implementation, and the concept of forest protection. The flow of thought by the theory of Van Meter and Van Horn which includes the Standards and Objectives, Resources, Characteristics or Nature of the Implementing Agency, Inter-Organizational Communication, Implementor Disposition and the Socio-Economic and Political Environment Research with qualitative methods, Research Location Balantak Forest Management Unit Banggai district, Research time for three months, Informants are elements of the Apparatus who implement the policy and Village Apparatus as the parties involved, Operational Definition Concept related to the model implementation of the policy. Types of qualitative data, and data sources are secondary data and primary data. The discussion clearly explains the implementation of forest protection policies in the Balantak KPH area, and concludes that the results of observations, interviews, documentation with stakeholders, as well as in-depth analysis of researchers in the field can be concluded that the implementation of forest protection policies in the Balantak Forest Management Area, Banggai Regency, Province Central Sulawesi has been running well, but there are still major problems, including in the aspect of;(1)Social, Economic and Political conditions of this aspect are the aspects that greatly influence the implementation of forest protection policies because the impact of this aspect is in the form of targeted forest utilization such as the development of tourism objects to improve the community's economy,pine forest management. (2)The basic measures,objectives of the policy,have not been maximized in implementation or application, in other words that the objectives of the policy are still partial, in this case the determination is the leader of the unit,(3) Human resources are still very lacking in mastery and have qualified skills so that they have not been able to compete and implement the latest regulatory policies,(4) Communication is still not optimal at the implementing and community stages, Policy determination, lack of socialization or communication by competent parties in implementing regulatory policies on forest protection and utilization.